A SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS OF MANAGEMENT PERFORMANCE - Aslinda; Sopiah (Transpublika Publisher, 2022)
Performance control is an critical a part of human capital control and a essential constructing block of erson overall performance. Performance control is the factor of controlling overall performance inside an organization. Employee overall performance, each in phrases of effectiveness, operations, and worker productivity, is inspired through the control competencies of a company's senior control. This is supported through administrative overall performance, which influences effectiveness and efficiency. The motive of this take a look at is to describe and talk overall performance control using the PRISMA method and techniques of econometric literature analysis. Journal screening using the PRISMA method resulting 30 journals with 76 authors. Results for these variables revealed that the variables were related to employee performance and leadership.